Morphology Controlled Magnetic Interactions of Porous Silicon Embedded Nanostructures. (18th February 2015) - Rumpf, Klemens; Granitzer, Petra; Koshida, Nobuyoshi; Poelt, Peter; Michor, Herwig
Abstract : In the frame of this work porous silicon templates with different morphologies, especially with respect to the roughness of the pore-walls have been fabricated and subsequently filled with diverse ferromagnetic metals to fabricate self-assembled three dimensional arrays of nanostructures (wires, particles) with distinct magnetic properties. The fabricated templates offer a quasi-regular self-assembled pore-arrangement with oriented pores. Also the pore-filling is self-assembled by electrochemical deposition and there are multiple possibilities to tailor the magnetic behavior of these systems such as material, morphology, inter particle distance or interfaces. One critical parameter for this purpose is the roughness of the pore walls and the surface of the metal structures, respectively. Within the pores of these templates ferromagnetic metals have been deposited and the modification of the magnetic properties correlated to the morphology of the different templates has been figured out.